Occupational exposure to electromagnetic fields, dietary and genetics factors and the risk of brain tumours: a UK case-control study - Demetriou, Lia (2010)
Nowadays, very little is known of the aetiology of brain tumours in adults and despite all efforts from scientists there is still a limited understanding of this disease. However, previous studies suggest that there is association between some genetic and environmental factors and adults’ brain tumours. Risk factors that have been considered to play a role in brain tumours aetiology are exposure to electromagnetic fields (EMF), diet, genetics, ionizing radiation, radio frequency exposure, occupational chemical exposure (pesticides and solvents), head trauma, viruses and it has also been suggested that factors such as allergies or influenza may be important. In this study a detailed literature review obtained for three risk factors; exposure to electromagnetic fields (EMF), diet and genetics.